Advancing stakeholder engagement in climate adaptation: a systematic review of structural barriers and operational enablers - Enora Bruley; Anna Scolobig; Marta Ellena; Sam Pickard; Mathilda Englund; Eulàlia Baulenas; Dmitry Erokhin; Sukaina Bharwani; Marina Mattera; Madeline Baldelli; Lucia Moreno; Judith Bielsa; et al. (Sustainability Science, 2026)

A new threat to Sardina pilchardus in the northwestern Mediterranean: Genetic validation of the presence of lethal parasites in pelagic eggs and ovaries - XÈNIA FRIGOLA-TEPE; NÚRIA PÉREZ-BIELSA; MARTA CABALLERO-HUERTAS; JUDITH OLLÉ-VILANOVA; MARTA MUÑOZ; JORDI VIÑAS (Mediterranean Marine Science, 2024)
Over the past few decades, the fishing industry and species conservationists have grown increasingly concerned about the decrease in catches and poor health of European sardines (Sardina pilchardus), particularly in the northwestern Mediterranean region. The species is threatened by a number of factors, including parasite illnesses, rising seawater temperatures, and overfishing. Increasing seawater temperatures due to climate change might lead to the proliferation of protistan parasites, such as Ichthyodinium chabelardi. This parasite has been documented in the literature to cause 100% larval mortality in sardines, which may have detrimental effects on fish populations and the fishing industry. We confirmed the existence of I. chabelardi in pelagic eggs and the ovaries of European sardines from the Catalan coast (northwestern Mediterranean) by means of stereomicroscopic analysis and a genetic methodology for parasite identification. The incidence of this infection was 22.5% in ovarian tissue and 11.5% in eggs. In this study, we present new data on the vertical transmission of I. chabelardi from one generation to another in sardines captured in the Mediterranean region. Interpreting outbreaks of I. chabelardi, especially in sardine populations, requires further research into the transmission of infection and improving our understanding of protozoan parasites.

Larval Retention and Homing Behaviour Shape the Genetic Structure of the Bullet Tuna (Auxis rochei) in the Mediterranean Sea - Judith Ollé-Vilanova; Núria Pérez-Bielsa; Rosa Maria Araguas; Núria Sanz; Sámar Saber; David Macías; Jordi Viñas (Fishes, 2022)
Background: The bullet tuna (Auxis rochei) is an epipelagic fish with a worldwide distribution that is highly targeted by fisheries. Genetic diversity and population genetics are good indicators of population structure and thus, essential tools for fisheries management. Knowing which factors (biotic and abiotic) might be shaping such structure is crucial for management plans. In the present study, we assessed the population structure of the bullet tuna in the western and central Mediterranean Sea. Methods: We used two types of genetic data: the mitochondrial DNA control region and seven microsatellite loci. The analysis of 431 sequences with a length of 386 bp from the mtDNA CR and the results from 276 individuals were genotyped by seven microsatellite loci. Results: Both types of markers coincided in showing significant genetic differences between an Iberian Peninsula–Strait of Gibraltar stock in comparison with a North African stock. Conclusions: We argue that this differentiation pattern is likely caused by reproductive strategies such as coastal spawning, larval retention, and natal homing behavior. These results should endorse the implementation of management plans for a resource that currently is not being managed. Thus, to ensure sustainability, these new policies should consider the presence of at least two genetically identified stocks.

Genetic validation of the unexpected presence of a tropical tuna, bigeye tuna ( Thunnus obesus ), in the Mediterranean - Nuria Pérez Bielsa; Judith Ollé; David Macías; Sámar Saber; Jordi Viñas (Journal of Fish Biology, 2021)
Bigeye tuna ( Thunnus obesus, Lowe, 1839) is one of the eight recognized species of the genus Thunnus . It is considered a tropical species distributed in the Atlantic, Pacific and Indian Oceans. To date, no validated presence of this species has been reported inside the Mediterranean Sea. This study, however, confirms, for the first time, the presence of three young individuals of this species within the Mediterranean Sea.